Evaluasi Kinerja Kapasitas Akses Pintu Tol Bandarkedungmulyo Jombang (Studi Kasus Simpang 3 Pintu Tol Bandarkedungmulyo Jombang) (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2021)
Congestion often occurs at road traffic intersections, especially at intersections at the Bandarkedungmulyo Jombang toll gate. This is due to the large volume of vehicles passing through the intersection. This study aims to find out about the performance of the road network at the 3 toll gate intersection for existing conditions, then analyze the road performance at the 3 toll gate intersection area and determine the appropriate traffic engineering so that it is expected to provide alternative solutions to the problems that occur. In this study, an analysis was carried out to find out the problems that occurred by conducting Road Performance Analysis from Traffic Volume data, reviewed based on Road Capacity, Degree of Saturation, Speed, and Road Service Level. In addition, BOK Vehicle Operational Cost Analysis was carried out. The results of the analysis show that the value of the Degree of Saturation V/C is 0.787 with a delay of 16.17 smp/second, and a minor delay of 60.20 smp/second, and the results of BOK Vehicle Operational Costs which are divided into 5 types of vehicles and groups, including: Goal I = Rp. 7,807,082,185,62 /year, Gol II Rp. 3.208.844.285.08 / year, Goal III = Rp. 8,929,702,224.79 / year, Goal IV = Rp. 1.307.684.578.63/year, Goal V = Rp. 8,924,181,682.37 /year